Exploring the effects of low‐level laser therapy on fibroblasts and tumor cells following gamma radiation exposure. Issue 11 (20th June 2016) - Ramos Silva, Camila; Cabral, Fernanda Viana; de Camargo, Claudinei Francisco Morais; Núñez, Silvia Cristina; Mateus Yoshimura, Tania; de Lima Luna, Arthur Cássio; Maria, Durvanei Augusto; Ribeiro, Martha Simões
Abstract : Ionizing radiation (IR) induces DNA damage and low‐level laser therapy (LLLT) has been investigated to prevent or repair detrimental outcomes resulting from IR exposure. Few in vitro studies, however, explore the biological mechanisms underlying those LLLT benefits. Thus, in this work, fibroblasts and tumor cells are submitted to IR with doses of 2.5 Gy and 10 Gy. After twenty‐four‐h, the cells are exposed to LLLT with fluences of 30 J cm –2, 90 J cm –2, and 150 J cm –2 . Cellular viability, cell cycle phases, cell proliferation index and senescence are evaluated on days 1 and 4 after LLLT irradiation. For fibroblasts, LLLT promotes – in a fluence‐dependent manner – increments in cell viability and proliferation, while a reduction in the senescence was observed. Regarding tumor cells, no influences of LLLT on cell viability are noticed. Whereas LLLT enhances cell populations in S and G2 /M cell cycle phases for both cellular lines, a decrease in proliferation and increase in senescence was verified only for tumor cells. Putting together, the results suggest that fibroblasts and tumor cells present different responses to LLLT following exposure to gamma‐radiation, and these promising results should stimulate further investigations.Senescence of tumor cells and fibroblasts on the 4 th day after ionizing radiation (IR) and low‐level laser therapy (LLLT) exposures. The number of senescent cells increased significantly for tumor cells (a ) while for fibroblasts no increment was observed (b ). The blue collor indicates senescence activity. Abstract : Low‐level laser therapy (LLLT) triggers different responses in tumor and normal cells previously exposed to ionizing radiation (IR). For fibroblasts, it is observed an increment in cell viability and proliferation. For cancerous cells, LLLT do not increase cell viability neither proliferation, but induces senescence. This study provides comprehension to consider LLLT as a therapy to be applied to regions known to have cancerous cells, after IR exposure.